Multichannel challenges for retail marketers - Reynolds, Jonathan (Henry Stewart Talks, 2009)
Challenging context for multichannel retailing, Effects of multichannel retailing on consumer behavior and demand, Multichannel retailing strategies and the implications for stores, Case studies of grocery retailing and general merchandise sectors, Future directions for multichannel activity